Unusual Phenotype and Disease Trajectory in Kearns–Sayre Syndrome - Josef Finsterer; Michael Winklehner; Claudia Stöllberger; Thomas Hummel (Case Reports in Neurological Medicine)
Objective. To describe unusual course and unusual phenotypic features in an adult patient with Kearns–Sayre syndrome (KSS). Case Report. The patient is a 49-year-old male with KSS, diagnosed clinically upon the core features, namely, onset before the age 20 of years, pigmentary retinopathy, and ophthalmoparesis, and the complementary features, namely, elevated CSF protein, cardiac conduction defects, and cerebellar ataxia. The patient presented also with other previously described features, such as diabetes, short stature, white matter lesions, hypoacusis, migraine, hepatopathy, steatosis hepatis, hypocorticism (hyponatremia), and cataract. Unusual features the patient presented with were congenital anisocoria, severe caries, liver cysts, pituitary enlargement, desquamation of hands and feet, bone chondroma, aortic ectasia, dermoidal cyst, and sinusoidal polyposis. The course was untypical since most of the core phenotypic features developed not earlier than in adulthood. Conclusions. KSS is a multisystem disease, but the number of tissues affected is higher than so far anticipated. KSS should be considered even if core features develop not earlier than in adulthood and if unusual features accompany the presentation.